Respostas
respondido por:
5
Formato:
(a - b)² = a² - 2a.b + b²
*******************************************
= (4x - 7)²
= (4x)² + 2.4x.(-7) + (-7)²
= 16x² + 8x.(-7) + 49
= 16x² - 56x + 49
__________________
Outra forma:
= (4x - 7)²
= (4x - 7).(4x - 7)
= 4x.4x + 4x.(-7) - 7.4x - 7.(-7)
= 16x² - 28x - 28x + 49
= 16x² - 56x + 49
*********************************
(a - b)² = a² - 2a.b + b²
*******************************************
= (4x - 7)²
= (4x)² + 2.4x.(-7) + (-7)²
= 16x² + 8x.(-7) + 49
= 16x² - 56x + 49
__________________
Outra forma:
= (4x - 7)²
= (4x - 7).(4x - 7)
= 4x.4x + 4x.(-7) - 7.4x - 7.(-7)
= 16x² - 28x - 28x + 49
= 16x² - 56x + 49
*********************************
BeaOliver123:
esse 2 saiu da onde ?
respondido por:
4
Olá,
(4x-7)² = (4x)² + 2(4x)(-7) + (-7)² = 16x² -56x + 49
(4x-7)² = (4x)² + 2(4x)(-7) + (-7)² = 16x² -56x + 49
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás